Mean reverting financial leverage: theory and evidence from Pakistan. Issue 5 (26th January 2016) - Ahsan, Tanveer; Man, Wang; Qureshi, Muhammad Azeem
Abstract: Grounding concepts of the two competing theories of capital structure (trade-off theory, pecking order theory) are quite opposite to each other. Trade-off theory claims that there is an optimal (target) capital structure and firms try to achieve that optimal (target) point. Whereas pecking order theory argues that there is no optimal (target) capital structure but the firms follow a specific pattern of financing. Using the two competing theoretic frameworks, this study applies Fisher-type panel unit root test to an unbalanced panel data of 13 115 firm-year observations of nonfinancial firms listed on Karachi Stock Exchange Pakistan spread over 38 years (1973–2010). Overall panel test results, for short-term, long-term, as well as total leverage support trade-off financing behaviour while individual firm results do not. Individual firm results show that only 16% of the firms have short-term target, 25% of the firms have long-term target and 12% of the firms have total target leverage ratio. Further, industry results explain that most of the industries do have target leverage ratios and classification of data into profitable and lossmaking firm-year observations explains that profitable firms clearly follow trade-off financing behaviour while the results for lossmaking firms do not support trade-off financing behaviour. Our study indicates that it is important for the government to ensure policies to develop well-balanced financial markets and to improve accountability systems.